MAN 7 Bireuen لترقية قدرة الطلبة على فهم التركيب الوصفي بـ Flash Card فعالية استخدام وسيلة (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
The aim of this research is to determine the effectiveness of using Flash Card to improve students' ability to understand At-Tarkib Al-Washfi at MAN 7 Bireuen, and also to determine student activities during the At-Tarkib Al-Washfi learning process using Flash Card. The research method used is an experimental method with a one-group pre-test and post-test design. As for tools for collecting data, researchers use observation and tests. The results of this research show that the use of Flash Card is very effective in improving students' ability to understand At-Tarkib Al-Washfi, with the results of the pre-test and post-test being at a significance level (sig. 2-tailed) of 0.000 < 0.05. This value indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. And student activity is very good when the learning process uses flash card. It is proven from the results of direct observations (observations) of student activities of 90‥. ranges from 80-100‥ in the very good category. This value shows that students responded well and participated actively in the Tarkib Wasfi learning process using flash cards.
Keywords: FlashCard; Learning At-Tarkib Al-washfi